Evaluation of Envisat ASAR IMP imagery for snow mapping at varying spatial resolution (Deception Island, South Shetlands – Antarctica) - Mora, Carla (2018)
Advanced synthetic aperture radar image mode precision (ASAR IMP) scenes of Deception Island from December 2008 to September 2010 have been analysed to assess its potential for snow cover classification. Backscattering was checked against ground truth. Despite the good spatial resolution of the ASAR, its applicability for detecting snow cover, and especially wet snow, was only possible at much lower resolutions, since noise was found to be very high. Scenes with bare ground or with dry snow cover showed highest backscattering, with averages from 210 to 212 dB. Wet snow showed a shift towards lower values, peaking at 215 dB. A threshold of 213 to 214 dB was identified between dry/bare ground and wet snow scenes at Crater Lake. The backscatter difference to a reference snow-free scene usually provided better classification results, and a threshold ranging from 22 to 23 dB was found. Results show that, despite the relative ease of use of C-band ASAR, special care is necessary since the results show significant noise, and it should only be applied to large areas. Large seasonal patterns of snow melt were identified on Deception Island.